PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN DIMEDIASI MOTIVASI KERJA (Studi Pada Karyawan Bidang Operasional PT. Bank Pembangunan Daerah Provinsi Jawa Timur Tbk Cabang Sidoarjo) - Adiwiratna Briandana Ganefanto Rachmat ; Prof. Dr. Noermijati, SE., MTM.Dr. Sudjatno, SE., MS.
Every company always makes changes gradually and continuously along_x000D_ with the times that have occurred. The purpose of these changes is to improve_x000D_ the performance of both employee performance and company performances in_x000D_ order to compete with other companies. The concept of change is influenced by_x000D_ two factors, namely internal factors, i.e. the company's ability to manage_x000D_ resources in hand effectively and efficiently, and external factors, i.e. the_x000D_ company's ability to adapt to current development. The purpose of this research_x000D_ is to examine and analyze the effect of the work environment and organizational_x000D_ culture on employee performance in the Operational Division of PT Bank_x000D_ Pembangunan Daerah Provinsi Jawa Timur Tbk, Branch of Sidoarjo, with the_x000D_ mediation of work motivation. _x000D_ The data of this quantitative study were obtained through distributing_x000D_ questionnaires to 134 respondents and were analyzed using the Partial Least_x000D_ Square method. The results of this research show that influential work_x000D_ environment significantly influences employee performance, organizational_x000D_ culture significantly influences employee performance, work environment _x000D_ significantly influences work motivation, organizational culture significantly_x000D_ influences work motivation, work motivation significantly employee performance._x000D_ In additon, motivation work partially mediates the influences of work environment_x000D_ on employee performance and the influence of organizational culture on_x000D_ employee performance. _x000D_ _x000D_ Keywords: work environment, organizational culture, work motivation, employee_x000D_ performance.